2010
DOI: 10.1021/jp107561s
|View full text |Cite
|
Sign up to set email alerts
|

Heats of Formation of C6H5, C6H5+, and C6H5NO by Threshold Photoelectron Photoion Coincidence and Active Thermochemical Tables Analysis

Abstract: Threshold photoelectron photoion coincidence has been used to prepare selected internal energy distributions of nitrosobenzene ions [C(6)H(5)NO(+)]. Dissociation to C(6)H(5)(+) + NO products was measured over a range of internal energies and rate constants from 10(3) to 10(7) s(-1) and fitted with the statistical theory of unimolecular decay. A 0 K dissociative photoionization onset energy of 10.607 ± 0.020 eV was derived by using the simplified statistical adiabatic channel model. The thermochemical network o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 129 publications
8
88
1
2
Order By: Relevance
“…In the very early stages of the development of the ATcT TN, when the network was much smaller, the resulting ATcT enthalpy of formation of N atom was strongly dominated by the same spectroscopic determination by Büttenbender and Herzberg [59]. Consequently, this determination was marked as a 'weak link' in the TN, and steps were undertaken to enhance the TN section surrounding N. Table 2) coincides with the previously reported [10] interim value. The CODATA [8] value is more than an order of magnitude less accurate and is 0.24 kJ/mol higher; perhaps a not entirely unrelated detail is that the bond dissociation energy explicitly quoted by CODATA should have produced an uncertainty for the enthalpy of formation of nitrogen atom of ±0.3 0 kJ/mol, but in the final analysis, the CODATA Task Group has decided for some reason to increase it to ±0.4 0 kJ/mol.…”
Section: Atct Values Forsupporting
confidence: 78%
See 3 more Smart Citations
“…In the very early stages of the development of the ATcT TN, when the network was much smaller, the resulting ATcT enthalpy of formation of N atom was strongly dominated by the same spectroscopic determination by Büttenbender and Herzberg [59]. Consequently, this determination was marked as a 'weak link' in the TN, and steps were undertaken to enhance the TN section surrounding N. Table 2) coincides with the previously reported [10] interim value. The CODATA [8] value is more than an order of magnitude less accurate and is 0.24 kJ/mol higher; perhaps a not entirely unrelated detail is that the bond dissociation energy explicitly quoted by CODATA should have produced an uncertainty for the enthalpy of formation of nitrogen atom of ±0.3 0 kJ/mol, but in the final analysis, the CODATA Task Group has decided for some reason to increase it to ±0.4 0 kJ/mol.…”
Section: Atct Values Forsupporting
confidence: 78%
“…4 Other than gradually gaining in accuracy as the TN was expanded over time, these ATcT values have not changed significantly since the previously reported versions [1,3,4,[9][10][11]. The CODATA value [8], subsequently adopted in the popular tables of Gurvich et al [12,13] and in the JANAF Tables 5 [14,15], was already quite accurate, D f H°2 98 (H) = 217.998 ± 0.006 kJ/mol, and thus in this particular case, the improvement in accuracy by almost three orders of magnitude is probably of no practical thermochemical consequence.…”
Section: Atct Values Formentioning
confidence: 77%
See 2 more Smart Citations
“…This is in good agreement with the previous harmonic results of Martin et al 16 Intensities of Renner-Teller subbands are shown in Table VII The enthalpy of formation at 0 K, ΔH f (0K), for X 2 Π 1/2 CCN was computed from the final zero-point energy corrected atomization energy (290.9 kcal/mol as calculated from the ΣD e value shown in Table I of 296.13 kcal/mol) together with spin-orbit corrections for both the molecule (+0.06 kcal/mol) and atoms (-0.14 kcal/mol), i.e., ΣD 0 = 290.8 kcal/mol. This is about 2 kcal/mol larger than the previously computed value by Martin et al 16 Using reference ΔH f (0K) values for the atoms 73 (170.024 kcal/mol for C and 112.469 kcal/mol for N), the resulting 0 K enthalpy of formation, 161.7 kcal/mol, is expected to be accurate to within about 0.5 kcal/mol, with the majority of this uncertainty arising from the higher order correlation contributions to the atomization energy.…”
Section: Pure Rotational and Ro-vibronic Intensitiescontrasting
confidence: 60%